Evil Itself and Nothingness in Proclus - Napoli, Valerio (Peitho. Examina Antiqua, 2020)
In his reflection on the nature of evil, the Neoplatonic philosopher Proclus affirms that evil itself (to autokakon) is “also beyond the absolute non-being” (epekeina kai tou mēdamōs ontos). With this assumption, he intends to reinforce the thesis of the non-existence of absolute evil, conceived as totally separate from good, and contrasted with the collateral and parasitic existence of evil mixed with good. He thus maintains a distinction between absolute evil and relative evil, conceived with reference to the distinction between absolute non-being (i.e., nothingness) and relative non-being. In Proclus, the thesis of the non-existence of absolute evil is presented as a necessary consequence of the non-dualist theory of evil in the sphere of a protology that identifies the first Principle of all things in the primary Good (identical to the supra-essential One), and which aims to reconcile the absolute primacy of the latter with the presence of evil in some orders of reality.